Against Anthropocentric: The Non-Human Other in Han Kang’s The Vegetarian - Rahma BENZINE (UNIVERSITÉ MOHAMED BOUDIAF - M’SILA, 2024)
Han Kang's The Vegetarian is a critically acclaimed literary masterpiece that delves into the intricacies of the relationship between humans and the non-human world. This dissertation employs post-humanist and ecofeminist theories to analyze the novel, offering a fresh and innovative perspective on the text. Through a detailed examination of the protagonist Yeong-hye's transformation and rebellion against societal norms, this study explores themes of identity and agency, revealing how the novel subverts traditional narratives that center on the assumed superiority of humans. The floral adornments and deep communion with nature represents a profound shift away from anthropocentric constraints, underscoring the interconnectivity and importance of all life forms. This work expands the discourse on the representation of the non-human in literature, contributing to a deeper comprehension of The Vegetarian's rich thematic depth. It offers insights into how the novel challenges preconceived notions of our relationship with the natural world and the urgency to rethink our anthropocentric views.
Keywords: Non-Human; Anthropocentric; Post-humanist; Ecofeminism; Identity and agency